Caracterização fitopatogênica, morfológica e Filogenética de isolados de fusarium preservados na Micoteca prof° Gilson Soares da Silva. - Oliveira, Leonardo de Jesus Machado Gois de (2021)
Microbial Collections are considered Biological Resource Centers and the ex situ preservation of microorganisms is an essential practice for the knowledge and use of biodiversity the choice of each preservation method must take into account the advantages and disadvantages offered by the method and the characteristics of each fungal species. The species of the genus Fusarium are known to exhibit high morphological similarity, and for not showing differences between pathogenic, non-pathogenic or saprophytic strains, therefore, the phylogenetic study through genes encoding proteins such as the elongation factor 1-α (EF-1α), the second largest subunit of RNA polymerase (RBP2), calmodulin and the β-tubulin gene (tub2). The objective of this thesis was to verify the preservation of the pathogenicity of Fusarium isolates in their respective hosts that are conserved in the different methods and to characterize isolates through the combination of morphology and phylogenetic relationships through four protein-coding genes. The isolates were preserved in three methods and the results of pathogenicity evaluation of F.oxysporum f. sp. lycopersici were preserved in the sterilized soil method MGSS 40, MGSS 41, MGSS 183, MGSS 225, and MGSS 233 were pathogenic to Santa Cruz tomato cultivars. The isolates MGSS 10, MGSS 221, MGSS 224, MGSS 226 and MGSS 277 preserved in the soil method were pathogenic to Abelmoschus esculentus cv. Valença in the 1st assay and in the 2nd assay the isolates preserved in the continuous subculture method MGSS 55, MGSS 226, and MGSS 323 were the most virulent to A. esculentus cv. Valencia. The isolates MGSS 324 and MGSS 325 preserved in the continuous transplanting method were pathogenic to banana varieties: 'Maçã Casca Verde', 'Maçã Turiaçu Amarela', 'Prata Anã' and 'Cacau Figo Cinza'. The isolate MGSS 60 preserved in the sterilized soil method was pathogenic to the cultivars of Vigna unguiculata 'BR-17 Gurguéia', 'BRS Tumucumaque', 'BRS Guariba' and 'Manteiguinha'. The isolate MGSS 329 preserved in the Castellani method was pathogenic to Passiflora edulis plants, while the isolates preserved in the continuous subculture method were not pathogenic. Pathogenicity test of isolates of F. oxysporum f. sp. coriandrii MGSS 415, MGSS 416 and MGSS 305 preserved in the continuous subculture method showed that the first two isolates were pathogenic to the cultivars of Coriandrum sativum: 'Verdão' and 'Verdão Super', and the isolate MGSS 305 was pathogenic to the cultivar 'Verdão Super '. The morphological characterization of the isolates shows variability in the shape and size of macro and microconidia and in the color of the colonies, with the presence of two groups of isolates: the first with the presence of short monophialides and the second group with the formation of mono and polyphialides. Molecular analysis of 58 isolates shows that 28 isolates belong to the Fusarium oxysporum species complex, 3 isolates belong to the Fusarium fujikuroi species complex and 27 isolates are not in any of the complexes established in the literature